Pro-poor groundwater development: the case of the Barind experiment in Bangladesh - Banerjee, Partha Sarathi; de Silva, Sanjiv (World Bank, 2020)
The Barind region, a water-stressed area in northwest Bangladesh, had an underdeveloped agricultural economy and high levels of poverty until two projects revitalized the area with enhanced groundwater irrigation. The Barind Integrated Area Development Project in 1985 and Barind Multipurpose Development Authority (BMDA) in 1992 used new water extraction technology and innovative management practices such as deep tubewells (DTWs) fitted with smart card–operated electric pumps to develop drought-resilient irrigation. Both projects have helped the Barind region reduce poverty and achieve self-sufficiency in rice. However, there are concerns about declining groundwater levels in the Barind and nearby regions, resulting in a temporary halt in DTW expansion. Preliminary evidence presented in this case study suggests farmers served by shallow tubewells (STWs) may be losing access to groundwater in some parts of the Barind region, which can have significant development implications because these tubewells remain the predominant source of irrigation. This evidence provides grounds to question whether an irrigation model reliant on DTWs is sustainable and equitable in the long term. Further research is needed to better establish groundwater conditions and understand the risk to STW users to inform future policy on DTW-driven agricultural development.